Anton Korošec, Slovenska ljudska stranka in Bolgari (1918–1941) - Vodopivec, Peter (Časopis za zgodovino in narodopisje, 2022)
The author recalls the commitment of the Slovene People’s Party, with Anton Korošec at its head, to the friendly relations of the Kingdom of the SHS and its state union with Bulgaria. The SLS even included the initiative for a state union with Bulgaria in its programme in 1923, and Korošec travelled to Sofia in 1927 at the King’s initiative and met with Bulgarian statesmen. When the Stojadinović government concluded a friendship pact with Bulgaria in 1936, it was enthusiastically welcomed by the SLS. In the years leading up to the Second World War, the idea of unification of the two countries was no longer discussed, but in autumn 1941, together with the Liberals, it was included in the programme sent to London.
Keywords: Anton Korošec; Croats and Serbs with Bulgarians; jugoslovansko-bolgarski odnosi; Korošec, Anton; SLS; Yugoslav-Bulgarian relations, unification of Slovenes; združitev Slovencev, Hrvatov in Srbov z Bolgari